Ultrafiltration and osmotic evaporation applied to the concentration of cholupa (Passiflora maliformis) juice - Forero Longas, Freddy; Vélez Pasos, Carlos Antonio; Sandoval Aldana, Angelica (Ingeniería e Investigación, 2013)
Cholupa it's an exotic fruit that has excellent organoleptic characteristics but highly sensitive to thermal treatments. Fruit was harvested in commercial fields and for each process stage, the following physicochemical parameters were analyzed: soluble solids, pH, total solids, viscosity, and turbidity. Was used a Pellicon2® ultrafiltration system (10 kDa) with flat membranes and filtration area 0.5 m2, osmotic evaporator had a polypropylene hydrophobic hollow fiber module MD020CP2N® with area 0.104 m2. Prior to ultrafiltration, in order to obtain a higher permeate flow, juice was subjected to enzymatic treatment with commercial mixtures, found that doses of Maxoliva® (50 µl/100g) and Rapidase® (40 µl/100g) are best treatment, which had a significant effect (P<0.05) reducing the viscosity and increase soluble solids; in clarification process by ultrafiltration, permeate flux rate has a behavior that fulfills Darcy law, with 19.4 and 6.0 l m-2 h-1, as maximum and minimum, respectively. Finally, osmotic evaporation process produce a concentrate of 65.15±0.36 oBrix with homogeneous appearance, dark yellow color, which when it's reconstituted dissolves easily in water. The results show that ultrafiltration and osmotic evaporation proved to be effective and synergistic technologies to get a good quality concentrate, that preserve much original characteristics of juice. This is the first work reported about cholupa juice processing.